Depression prevalence and estimation of psycholocial parameters within adult population in city of Zagreb - Stojanović-Špehar, Stanislava; Blažeković-Milaković, Sanja; Amerl-Šakić, Vjekoslava; Kolić, Nejra; Šupe, Svjetlana (2009)
There is no data on depression prevalence in Croatia. The aim of this study was to establish the prevalence and psychosocial risk factors of depression in the adult population of the Croatian capital Zagreb, particularly in patients suffering from Depressive episode (F32) and Recurrent depressive disorder (F33). Subjects and methods: A cross-sectional study was preformed on a representative sample for city of Zagreb drawn from 10 family physicians’ offices with 17290 patients. From standardized medical files, the family physicians sorted out data of patients with depression, both Depressive episodes (F32) and Recurrent depressive disorder (F33), classified according to ICD 10. Psychosocial parameters were assessed according to the core questions for the management of psychosocial risk factors recommended by the European Guidelines on Cardiovascular Disease Prevention in Clinical Practice.Depression had a prevalence of 2.2%. It was poorly recognized, as were some psychosocial factors especially genealogical disease burden. This suggests the need for implementation of special intervention methods of developing the family physicians‘skills in adopting the psychosocial approach to depressive patients with a focus on recognized psychosocial risk factors
Bibliografija: 34 jed
Keywords: Depresija -- Prevalencija -- Obiteljski liječnik; Zagreb